1996
DOI: 10.1007/bf02044107
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness polyneuropathy in multiple organ dysfunction syndrome and weaning from the ventilator

Abstract: Axonal polyneuropathy is related to the severity of multiple-organ-dysfunction syndrome. Its presence does not necessarily implicate difficult weaning from artificial ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(27 citation statements)
references
References 39 publications
3
23
0
1
Order By: Relevance
“…Confirmed risk factors for CIP are sepsis, SIRS and MOF [7, 11, 1820]. CRP, a marker for SIRS [21] and sepsis [22, 23], were increased in nearly all cases of the present study, indicating systemic inflammation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Confirmed risk factors for CIP are sepsis, SIRS and MOF [7, 11, 1820]. CRP, a marker for SIRS [21] and sepsis [22, 23], were increased in nearly all cases of the present study, indicating systemic inflammation.…”
Section: Discussionsupporting
confidence: 61%
“…It is known that mechanical ventilation is associated with CIP [9, 18]. In this study, 79% of all patients had been on mechanical ventilation before or during early rehabilitation.…”
Section: Discussionmentioning
confidence: 93%
“…Some investigators have observed a significantly higher mortality in patients with CIP compared to patients in the ICU with similar APACHE III scores but who did not have neuropathy Table 4 Features of critical illness polyneuropathy. Neurocritical Care ♦ Volume 3, 2005 (172,176,178) ; however, this finding has not been confirmed by others (35) . A prospective study of 73 patients with sepsis demonstrated that patients with CIP required ventilator support for an additional 12 days (median value), remained in the ICU an additional 19 days, and remained in the hospital an additional 52 days compared to patients without neuropathy (178) .…”
Section: Critical Illness Polyneuropathymentioning
confidence: 70%
“…Older studies have found a strong correlation between the severity of the neuropathy and duration of ventilator dependence, severity of multi-organ failure, and number of different organs involved (35,172,176) . However, others have found no correlation between electrophysiological abnormalities and length of stay in the ICU or time on the ventilator.…”
Section: Critical Illness Polyneuropathymentioning
confidence: 99%
See 1 more Smart Citation